Six-Port Receiver Analog Front-End: Multilayer Design and System Simulation - Winter, Sebastian; Kölpin, Alexander; Weigel, Robert (IEEE Transactions on Circuits and Systems II: Express Briefs, 2008)
In this paper, a six-port receiver analog front-end structure based on a Wilkinson power divider and three hybrid couplers is presented, which has been implemented in a multilayered, meandered manner, yielding a size reduction of about 78% compared to a planar design. The measured S-parameters of the new design are in good accordance with simulated S-parameters of the planar structure. System simulations with an orthogonal frequency division multiplexing signal show the suitability of the design for six-port communications receivers.
elib2cris::1512001600,winter2008a
Keywords: OFDM modulation; S-parameters; power dividers; radio receivers; S-parameters; Wilkinson power divider; hybrid couplers; planar structure